Transitioning from an occupational therapy student to a clinically competent occupational therapist – A qualitative study - Patrik Sjöberg; Annika Lexén (Scandinavian Journal of Occupational Therapy)
Background The transition process from being an occupational therapy student to becoming an occupational therapist has been shown to be stressful, with an increased risk of burnout and job turnover. Consequently, there is a need to gain a deeper understanding of this process in order to identify ways of making it easier.Aims/objectives To describe newly graduated Swedish occupational therapists’ experiences of the transition from being an occupational therapy student to becoming a clinically competent occupational therapist.Material and methods A qualitative study involving 15 participants was conducted using interviews to collect data and content data analysis was undertaken to capture occupational therapists’ experiences of the transition process.Results A theme emerged: ‘Bridging the gap by seeking stability in the transition from occupational therapy student to clinically competent occupational therapist’, with two sub-themes, 1) ‘Facing a new reality’ and 2) ‘Establishing one’s role’, containing categories that encapsulated experiences of the transition.Conclusions and significance To bridge the gap in the transition process, universities could review their curricula to identify changes to better prepare newly graduated occupational therapists for the demands of clinical practice. Employers hiring new graduates need to offer comprehensive orientation and access to mentorship for support.